Gellan Gum Spongy-like Hydrogels Reinforced with Hydroxyapatite for Bone Tissue Engineering Applications - Maia, F. Raquel (2017)
Bone tissue engineering with cell-laden-hydrogels has been attracting attention worldwide. In fact, they can resemble in some aspects the extracellular matrix, as high water content. In a forward thinking manner, our group engineered gellan gum (GG) spongy-like hydrogels where cells adhered and proliferated without the need of any modification. Moreover, we took advantage of these characteristics and combined it with hydroxyapatite to reinforce the GG (GG-HAp) spongy-like hydrogels. Since there is limited knowledge about the interaction of osteoclasts with biomaterials, we assessed the ability of developed matricesto support osteoclastogenesis. After mechanical and morphological characterization, bone marrow cells were seeded and treated with 1,25-dihydroxyvitamin D3 (Vitamin D3) to promote osteoclastogenesis. After 7 days, cell viability and differentiation was assessed. It was shown that the addition of HAp to GG spongy-like hydrogels enable the formation of lager pores and thicker walls and the improvement of the mechanical properties (stiffness). Additionally, cells were viable and metabolically active. Finally, it was observed that the GG-HAp spongy-like hydrogels supported cell differentiation into pre-osteoclasts, as suggested by the presence of aggregates of TRAP-stained cells, and the expression of DC-Stamp and Cathepsin K, necessary for cell fusion and resorption capacity, respectively.Â  Overall, GG-HAp spongy-like hydrogels showed to support osteoclastogenesis, an important feature when establishing new biomaterials for bone tissue applications.Â Â